GROWTH AND SURVIVAL RATE OF GOLDEN TREVALLY, Gnathannodon Speciosus Forsskal WITH DIFFERENT LENGTH SIZE - Anak Agung Alit (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
Golden travelly is a type of fish that can live on the surface, belongs to Carangidae family, for a length of 5-8 cm can function as marine ornamental fish with the name of yellow crime or yellow samba, and can be  used for consumption. The study was conducted to determine the effect of length on the initial stocking of fish seed to the growth and survival rate of golden travelly. Fish samples were cultured fish golden travelly of 45 days old hatchery and stocked with density of 300 pc/tank in 9 tanks with volume of 1 m³ feber/tanks. Golden travelly were fed with commercial fish by feeding frequency of 3 times/day untill satiation. The tested treatments were based on initial different lengths i.e., treatment A (1.5 to 2.0 cm/pc), B (2.5 to 3.0 cm/pc), and C (3.5 to 4,0 cm/pc). Feeding was based on 10-15 % of body weight. Measured variables were body length growth, survival rate, and quality of water. Growth and survival rate were analysed using analyses of variance (ANOVA). The results showed that the growth rate of fish golden travelly Gnathannodon speciosus Forsskal was best at treatment B (2.5 to 3.0 cm/pc) with 7% per day and 92% survival rate. Keywords: fish seed golden trevally, tanks , growth, and survival.